Technology Transfer of Compost Briquette Production from Household Organic Waste in Sawah Lebar Baru Sub-District: Alih teknologi pembuatan briket kompos dari limbah organik rumah tangga di kelurahan sawah lebar baru - Yovan Witanto; Agus Nuramal; Helmizar (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
Compost produced by economically non-productive residents in Sawah Lebar Baru Subdistrict has remained underutilised, leading to accumulation and limited economic benefit. This community service activity aimed to introduce Seed Briquette Technology as an innovative solution to enhance the value and usability of household compost. The programme involved knowledge dissemination and hands-on training on how to produce seed briquettes using existing compost. The compost was compacted into Soil Blocks—pressed blocks with a central hole—using a manual moulding tool. This tool was introduced and distributed to local residents during a technology transfer session conducted by the Faculty of Engineering in RT 29. The participants responded with strong interest and demonstrated the ability to apply the technique successfully. Community members were able to convert their compost into functional seed briquettes, showcasing both skill development and successful adoption of the technology. As a result, the participants gained valuable technical skills which are expected to support future income generation. The activity highlights the potential of simple, locally adapted technologies to improve waste management and economic empowerment in urban communities.